2015
DOI: 10.1002/iub.1467
|View full text |Cite
|
Sign up to set email alerts
|

miR‐4299 mediates the invasive properties and tumorigenicity of human follicular thyroid carcinoma by targeting ST6GALNAC4

Abstract: Altered sialylation is closely associated with tumor progression and invasiveness. Micro-RNAs endogenous regulators of gene expression have been implicated in human thyroid carcinoma invasiveness. The objective of this study is to examine the alterations of miR-4299 and ST6GALNAC family in human follicular thyroid carcinoma during metastatic process. qRT-PCR showed the differential expressional profiles of miR-4299 and ST6GALNAC family in three kinds of thyroid cell lines (FTC-133,FTC-238, Nthy-ori 3-1) and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…ST6GALNAC2 regulates breast cancer invasion 40 , 41 . In FTC research, we found that ST6GALNAC4 and ST6GALNAC2 modulate tumourigenicity of FTC 17 , 42 and that miR146a/b promotes FTC cell proliferation via the inhibition of ST8SIA4 16 . In the current study, ST6GAL2 was more highly expressed in FTC tissues and cell lines compared with normal tissues and cell lines.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…ST6GALNAC2 regulates breast cancer invasion 40 , 41 . In FTC research, we found that ST6GALNAC4 and ST6GALNAC2 modulate tumourigenicity of FTC 17 , 42 and that miR146a/b promotes FTC cell proliferation via the inhibition of ST8SIA4 16 . In the current study, ST6GAL2 was more highly expressed in FTC tissues and cell lines compared with normal tissues and cell lines.…”
Section: Discussionmentioning
confidence: 96%
“…In previous studies, protein synthesis was shown to be modulated by miRNAs that are able to bind to the 3′-untranslated region of target mRNAs 15 . According to our previous research, miR146a/b promotes FTC cell proliferation via the inhibition of ST8SIA4; 16 moreover, miR-4299 regulates FTC cell invasiveness by targeting ST6GALNAC4 17 . In addition, increasing experimental evidence suggests that lncRNAs functionally target miRNAs, which can be sponged by lncRNAs.…”
Section: Introductionmentioning
confidence: 87%
“…Research on this remains limited, but some recent studies investigated functional relationship of sialic acid phenotypes and malignant character of thyroid cancers. The suppression of the ST6GalNAc IV enzyme using miRNAs in follicular carcinoma cell lines significantly reduced their invasive and malignant characters . In addition, it has been reported that blocking the activity of the phosphotidylinositol 3‐kinase (PI3K)/Akt signaling with specific inhibitors results in the inactivation of the ST6GalNAc II enzyme, thereby reducing the invasive character of follicular cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…The suppression of the ST6GalNAc IV enzyme using miRNAs in follicular carcinoma cell lines significantly reduced their invasive and malignant characters. 16 In addition, it has been reported that blocking the activity of the phosphotidylinositol 3-kinase (PI3K)/Akt signaling with specific inhibitors results in the inactivation of the ST6Gal-NAc II enzyme, thereby reducing the invasive character of follicular cancer cells. 17 The residues of α1,6 fucose are found in the initial GlcNAc molecule of N-linked oligosaccharides and transferred to this molecule by the enzyme FUT8.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that miR-4701-5p is responsible for multi drug resistance of chronic myeloid leukemia cells, at least in part, by targeting and down-regulating ST3GAL1 [103]. The invasive properties and tumorigenicity of human follicular thyroid carcinoma is mediated by miR-4299, through targeting and silencing ST6GALNAC4 [104]. …”
Section: Epigenetic-regulation Of Cancer Associated Structuresmentioning
confidence: 99%